High speed deformation and break-up of shaped charge jets - Welsh, B.S. (1993)
Jets resulting from shaped charges which contain metal liners are able to penetrate hard or armoured targets. Their penetration performance is related to the density of the jet and target material and also the length to which the jet can elongate. Models that describe the processes involved have generally assumed hydrodynamic fluid flow and as such have been very successful in most cases. However, the break-up of jets has proved to be inconsistent with the fluid flow models and cannot be accurately described. Break-up is important since it is the final phenomenon in tensile deformation and therefore represents the limiting extent of jet elongation. Additionally, following break-up the jet fragments are particularly susceptible to lateral velocities and tumbling which dissipate the jets energy and further reduce its penetration performance.